Optimization of potassium fertilization/nutrition for growth, physiological development, essential oil composition and antioxidant activity of Lavandula angustifolia Mill - Chrysargyris, Antonios; Drouza, Chryssoula; Tzortzakis, Nikos G. (My University, 2017)
Lavandula angustifolia (Mill.) is a medicinal plant of great importance with a variety of applications in perfume and pharmaceutical industries or landscaping, but only limited information is available about its response to potassium supplementation. This experiment was conducted in order to determine the effects of potassium (K: 275-300-325-350-375 mg L-1) levels on the morphological and biochemical characteristics of lavender grown hydroponically. Results showed that K levels affected plant growth, mainly the root development while no differences were found for leaf chlorophyll content and stomatal conductance. Essential oil yield increased in the 300 mg L-1 in comparison to 275 or 325-375 mg L-1 of K application. The middle ranged K levels (300-325-350 mg L-1) enhanced leaf content in total phenols, flavonoids and antioxidant activity (DPPH, FRAP). Lipid peroxidation content (MDA) employed as damage index, was lower in the 325 mg L-1 of K treatment. No differences were observed in antioxidant enzymes (SOD, CAT, APX) activity and H2O2 content among K applications. The main constituents of leaves essential oil (1,8-cineole, borneol, camphor, α-terpineol, myrtenal) and mineral accumulation were affected by K treatments. Lavender grown in 300 mg L-1 of K was appropriate for the essential oil uses/production while the 325 mg L-1 of K were more appropriate for lavender cultivation for fresh and dry matter uses.
Keywords: Antioxidants; Essential oil; Lavandula angustifolia; Minerals; Soilless culture